menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Which of the following equations is the result after the first step in solving 3x + 6 = 12? x + 6 = 4 x = 3 3x = 18 3x = 6
asked
Jun 14, 2022
98.1k
views
0
votes
Which of the following equations is the result after the first step in solving 3x + 6 = 12?
x + 6 = 4
x = 3
3x = 18
3x = 6
Mathematics
college
Maurice Klimek
asked
by
Maurice Klimek
5.1k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
2
Answers
7
votes
Explanation:
3x=6 would be your answer
Mayankcpdixit
answered
Jun 15, 2022
by
Mayankcpdixit
5.6k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
6
votes
3x=6 is the answer after solving the first step in the equation
Txs
answered
Jun 19, 2022
by
Txs
5.2k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.6m
questions
7.3m
answers
Other Questions
What is the value of x? (-4) - x = 5
1/7 + 3/14 equivalent fractions
185g in the ratio 2:3
(3x1,000,000)+(3x100,000)+(2x100) what is this number written in standard form?
The function h = -t2 + 95 models the path of a ball thrown by a boy where h represents height, in feet, and t represents the time, in seconds, that the ball is in the air. Assuming the boy lives at sea
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org